(untitled) (International Journal of Engineering and Computer Science, 2015)
Transactions in real-time databases should be scheduled considering both data consistency and timing constraints. In addition, a real-time database must adapt to changes in the operating environment and guarantee the completion of critical tasks. The effects of scheduling decisions and concurrency control mechanisms for real-time database systems have typically been demonstrated in a simulated environment. Many time-critical applications data may be distributed among multiple sites. For example, such applications include command and control, industrial automation, aerospace and defense systems, telecommunications, banking, etc. In such applications, it imperative that the data be available to the requesting transactions at the time it is needed. In a typical distributed database, the transaction is required to access the remote data directly, at the risk of missing its deadline. Another problem can occur in such a scenario when the requesting transaction accesses the data, but it is not temporally valid. That is, its value is “out-of-date” because the transaction did not read from the most recent update. A replication algorithm creates replication transaction based on client’s data requirements in a distributed real time databases. These replication transaction copy data objects to the site on which they are needed just in time for the deadline to occur. The algorithm carefully computes the parameters of the replication transactions so that we can guarantee that any requests that read data, in fact, read temporally valid data. This algorithm is designed to work in a static environment in which all object locations, and client data requirements are known a priori.